Analyzing the global population crisis : asking questions, evaluating evidence, and designing solutions - Steele, Philip, 1948- (Steele, Philip, 1948- Analyzing environmental change., 2019)
Discusses the idea that the global population is getting to large to sustain, offering evidence to back up this position, and discussing solutions people have put forth to help prevent the population growth from damaging and limiting the freedom, peace, and human rights of people around the world. Includes a glossary.